The Effect of Product Quality, Price, Shop Atmosphere, and Service on Coffee Shop Consumers' Purchase Decisions - Felix Tri Wicaksono; I Ketut Suamba; I Gede Setiawan Adi Putra (IJESS International Journal of Education and Social Science, 2026)
The rapid growth of independent modern coffee shops in Denpasar City has transformed the competitive landscape from transactional orientation toward an experience-based economy (third place). This study aims to analyze consumer perceptions and examine the direct and indirect effects of product quality, price, store atmosphere, and service on purchase decisions through the mediating role of customer satisfaction. Employing a quantitative explanatory approach, the research surveyed 100 consumers of modern independent coffee shops in Denpasar City, selected via purposive-accidental sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Descriptive findings indicate that price and purchase decision are perceived at a high level, whereas product quality, store atmosphere, service, and customer satisfaction are rated at a moderate level. Inferentially, all independent variables exert positive and significant effects on both customer satisfaction and purchase decision. Store atmosphere emerges as the strongest predictor of customer satisfaction (? = 0.489; f² = 0.553, large effect), while price demonstrates the strongest direct influence on purchase decision (? = 0.246). Customer satisfaction functions as a complementary partial mediator, with the largest mediation effect occurring through the store atmosphere pathway (60.3% of total effect). The structural model explains 57.4% of the variance in customer satisfaction and 65.4% in purchase decision. The study concludes that consumer purchase decisions in Denpasar's coffee shop sector are shaped by two simultaneous pathways: a transactional pathway driven by price efficiency, and an experiential pathway consolidated through affective satisfaction. These findings reveal a phenomenon of spurious loyalty high visitation frequency coupled with moderate emotional commitment highlighting the vulnerability of behavioral retention in a hyper-competitive market with low switching costs. Practical implications suggest that coffee shop managers should prioritize (1) servicescape optimization, particularly spatial comfort and authentic integration of Balinese cultural identity; (2) supply chain coordination to ensure product consistency from upstream farmers to downstream service delivery; and (3) enhancement of service responsiveness and personal connection to transform transactional visits into sustained relational loyalty. From an agribusiness perspective, the study underscores the strategic importance of linking upstream coffee production quality with downstream consumer experience to ensure long-term market sustainability.